Conversion Coatings - Bibber, John W. (Cambridge Scholars Publisher, 2019)
This book is a guide to all new and presently existing processes available to chemically modify the surfaces of industrially used metals. The modifications described here will produce hard scratch-resistant surfaces, corrosion-resistant surfaces, and surfaces that will easily accept applied coatings, such as industrial paints. Included in the book are processes for aluminum, magnesium, titanium, iron, copper, and silver and their respective alloys, as well as a number of other metals and their related alloys.